Implikasi Hukum Kreditur Menangkal Pailit Yang Diajukan Debitur Berdasarkan Putusannya Nomor 33/PAILIT/2004/PN. NIAGA.JKT.PST - Saija, Ronald; Radjawane, Pieter (Pusat Kajian Hukum Bisnis Fakultas Hukum Universitas Pattimura, 2024)
This study aims to understand how the settlement of bankrupt assets is conducted concerning debtors filing for their bankruptcy. The case begins with the debtor's inability to repay their debts, leading them to declare bankruptcy. This research employs a normative juridical approach, prioritizing library research and document analysis to obtain secondary legal materials. The normative approach examines legal regulations related to the issue of legal protection for creditors concerning bankruptcy filed by debtors. Meanwhile, the juridical approach is used to analyze legal facts to address issues related to the protection of creditors' rights in connection with debtors declaring bankruptcy. The Bankruptcy and Suspension of Debt Payment Obligations Act (UUKPKPU), which replaced the previous Bankruptcy Act (UUK), remains insufficient in fully protecting creditors' rights. In the dispute involving PT. Golden Adishoes, there is a lack of clarity regarding the full repayment of debts, particularly when the bankrupt debtor's assets are insufficient to settle all their obligations. This situation implicitly forces creditors to accept that the bankrupt debtor cannot fully repay their debts. Furthermore, there is no explicit guidance or solutions provided for creditors to take action before the bankruptcy petition is filed by the debtor in the Commercial Court.